Research Hotspots and Trends in Acupuncture for Cancer:A bibliometric analysis from 2004 to 2024 - Ji Z; Niu H; He A; Li K; Jia J; Zhang M; Liu G (Journal of Multidisciplinary Healthcare)
Zhe Ji,* Heyuan Niu,* Anqi He, Kaiyu Li, Jinyan Jia, Maorun Zhang, Gang Liu Department of General Surgery, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Liu, Email lg1059@tmu.edu.cnBackground: Acupuncture is increasingly recognized as a promising intervention modality in cancer treatment. Nevertheless, there has been a paucity of systematic analysis and visualisation of relevant publications through bibliometric methods. This paper conducts a bibliometric analysis of research on acupuncture within the realm of oncological applications, aiming to explore its prospects and emerging trends.Methods: In this study, we analyzed 2117 documents obtained from the Web of Science Core Collection (WOSCC) to examine the correlations among authors, journals, institutions, countries, and keywords. This analysis was conducted using the Bibliometric R package, CiteSpace, and VOSviewer software.Results: The evolution of acupuncture can be broadly divided into three time periods: 2004– 2008, 2009– 2017 and 2018– 2024. The WOSCC retrieved 2117 publications on acupuncture for cancer over the past 20 years. Among the top 10 institutions, seven were from the United States, two from China, and one from Korea. Memorial Sloan Kettering Cancer Center had the highest number of publications. At the same time, the journal INTEGRATIVE CANCER THERAPIES published the most articles in this field. Keyword co-occurrence analysis revealed four distinct clusters: “Alternative and Complementary Medicine for Cancer”, “Acupuncture for cancer-related fatigue and pain”, “Acupressure for anxiety, depression, and insomnia”, “Improving quality of life for breast cancer patients”. The most recent keyword outbreaks included “sleep”, “radiation induced xerostomia”, “recovery”, “insomnia”, and “induced peripheral neuropathy.” Breast cancer is the type of cancer for which acupuncture is most commonly used.Conclusion: The future research focus will be on acupuncture as a treatment for sleep disorders, the alleviation of radiotherapy complications and the improvement of postoperative quality of life. Research on acupuncture in the field of breast cancer is more extensive compared to other cancers. Therefore, it is necessary to strengthen research on acupuncture in different cancer types.Keywords: acupuncture, bibliometric analysis, cancer, citespace, VOSviewer